Democratic Republic of Congo : Evaluation of the Technical Assistance Program (May 2001 to April 2004) and of Areas for Further Assistance to the Central Bank of Congo. (Policy Papers; Policy Paper ;, 2006)
This report discusses the results of the evaluation of the MFD technical assistance program with the BCC. The evaluation covered the period May 2001-April 2004 and focused on foreign exchange and monetary operations, internal audit, accounting, banking supervision. It was conducted during December 14-17, 2006 in conjunction with an MFD advisory mission. The mission examined the implementation of this program by two (2) resident experts (a general advisor to the Governor and a resident advisor responsible for internal audit), three (3) multitopic missions, and ten (10) short-term expert visits.1.